Analisis Variasi Layout Shearwall Dengan SNI 1726-2019 Terhadap Perilaku Bangunan Bertingkat (Studi Kasus: Gedung Pelayanan Publik Satu Atap Bandar Lampung) - Setiawan, Andi; Isneini, Mohd.; Noorhidana, Vera Agustriana; Husni, Hasti Riakara (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
Earthquake resistant buildings are not designed only by strengthening the resistance of the structure, but are also designed to reduce earthquake forces. One of the structural reinforcement elements that can reduce earthquake forces is shearwall. The variation of shearwall layout will have a different effect on the performance level of the structure. This study aims to determine the performance level of the structure with a variety of shearwall layouts in a building structure model using the pushover analysis method. Determining the level of structural performance using pushover analysis is carried out using the help of structural analysis programs based on SNI 1726-2019, SNI 1727-2020, SNI 2847-2019 and ATC-40. From the research results it was found that the structural performance level according to ATC-40 (1996), for model 1 and model 6 were included in the damage control category, while for model 2, model 3, model 4 and model 5 were included in the immediate occupancy category. Placement of shearwall which has the optimum value according to ATC-40 for the X direction occurs in model 2 with the shearwall installed in an L shape which is placed near the center of mass of the building. Whereas in the Y direction it occurs in model 3 with the shearwall installed in an L shape which is placed away from the center of mass of the building. Key words : shearwall, model, structure performance level, pushover analysis.